EFL University Students' Perceptions of Shadowing Technique for Developing Speaking Skills - Aisyah Ririn Perwikasih Utari; Jay Ar Cristobal (ALACRITY : Journal of Education, 2025)
Investigating University students’ perceptions of shadowing technique is the aim of the study to develop their speaking skills. There are 25 students of the third semester or second year in the class who become the participants of the research. Their learning process of speaking using shadowing technique in all classroom activities in ten weeks which is integrated in Speaking for Daily Communication Course. Feedback and reflections from the students are used for the research data. The research findings are dominantly positive with the aspects of effectiveness, accessibility and flexibility for independent practice for the sake of fluency and pronunciation improvement, and natural repetition of the shadowing activities. Intermediate level students get more benefit of the technique, the high ones also get significance refinement, and the low-achieved students finds the technique helpful for their initial step to improve their speaking skill significantly. Empirical proofs are reported as conclusion that shadowing technique can provide insightful findings that educators can implement it in speaking course.